Social Stigma in the Short Film Tilik: An Analysis of Tzvetan Todorov's Three Semiotic Levels (Oratio Directa, 2023)
Film functions both as art and as a medium for communicating social messages. This qualitative descriptive study analyzes the construction of social stigma in the short film Tilik through Tzvetan Todorov's three semiotic levels. The analysis shows that the film represents social stigma embedded in everyday community interaction. Internet and social-media information intensifies stigma toward particular individuals, especially when audiences lack adequate media literacy and become both producers and consumers of misinformation.
Keywords: Semiotics; Tzvetan Todorov; Short film; Tilik; Social stigma